Relationship Between Illness Representations and Symptoms of Internet Gaming Disorder Among Young People: Cross-Lagged Model - Xue Yang; Kei Man Wong; Rui She; Chengjia Zhao; Nani Ding; Huihui Xu; Xiaolian Tu; Xinyi Lai; Guohua Zhang (JMIR Publications, 2021)
BackgroundThe common-sense model of illness suggests that mental representations of health threats may affect one's behavioral reactions to them and health status. Internet gaming disorder is a newly defined mental disorder. Illness representations of internet gaming disorder may affect one's risk of internet gaming disorder. In turn, symptoms of internet gaming disorder may affect one's perceptions of the disorder. ObjectiveThis study aimed to investigate the relationships between illness representations and symptoms of internet gaming disorder in college students. MethodsA 1-year longitudinal study was conducted with a convenience sample of Chinese college students (n=591; 342/591, 57.9% female). ResultsOf the participants, 10.1% (60/591) and 9.1% (54/591) were classified as having probable internet gaming disorder at baseline (T1) and follow-up (T2), respectively. The correlations between some dimensions of illness representations regarding internet gaming disorder (ie, consequence, timeline, personal control, treatment control, and concern) at T1 and symptoms of internet gaming disorder at T2 and between symptoms of internet gaming disorder at T1 and the dimensions of illness representations at T2 (ie, consequence, timeline, personal control, and emotional response) were statistically significant. The cross-lagged model fit the data well ((χ2/df=2.28, comparative fit index=.95, root mean square error of approximation=.06) and showed that internet gaming disorder at T1 was positively associated with unfavorable illness representations at T2. ConclusionsIndividuals with more severe symptoms of internet gaming disorder had more pessimistic perceptions about the disorder. Such cognitive perceptions may affect one's emotional and behavioral reactions towards the disorder (eg, greater levels of depression and low self-control intention) and should be modified by educational programs and psychological interventions.